Effect of Functional Carbon Nanotube Fillers on the Physical and Thermal Characterization of Radiation Curable Coating - Khairi, Khairul Aiman; Harun, Mohd Hamzah; Othman, Norfazlinayati; Mohamed, Mahathir; Alias, Mohd Sofian; Rahman, Mohd Faizal Abd; Umar, Khairil Nor Kamal; Tajau, Rida; Ismail, Nor Batrisya; Zaharuddin, Izzuddin Mohamad; Aminuddin, Siti Nur Eyisha Wafa Mohd (Journal of Material Science and Radiation, 2025)
This work investigates the formulation of a radiation-curable coating that integrates functionalized carbon nanotubes (f-CNT) to improve surface characteristics. Trimethylolpropane triacrylate (TMPTA) was employed as the monomer, with epoxy acrylate and urethane acrylate as oligomers and Irgacure-500 as the photoinitiator. To cure the coatings, the formulations were subjected to ultraviolet (UV) light, and the surface properties were investigated using Fourier-transform infrared spectroscopy (FTIR), pendulum hardness testing, and thermogravimetric analysis (TGA). The results show that altering the ratios of f-CNT in the formulations have a considerable impact on the mechanical and thermal characteristics of the coating. The findings show that ideal compositions of these additives improve the hardness, crosslinking density, and thermal stability of the cured films, offering insight into their potential